Cytogenetics of extramedullary manifestations in multiple myeloma. (1st February 2013) - Billecke, Lisa; Murga Penas, Eva M.; May, Annette M.; Engelhardt, Monika; Nagler, Arnon; Leiba, Merav; Schiby, Ginette; Kröger, Nicolaus; Zustin, Jozef; Marx, Andreas; Matschke, Jakob; Tiemann, Markus; et al.
Summary Extramedullary disease in patients with multiple myeloma is a rare event, occurring mostly in advanced disease or relapse. Outcome is poor and prognostic factors predicting the development of extramedullary disease have not been defined. We investigated cytogenetic alterations of myeloma cells in different extramedullary manifestations by adapting the fluorescence in situ hybridization (FISH) technique in combination with cytoplasmic immunoglobulin staining to study the cytogenetics of plasma cell tumours on paraffin embedded material. Thirty six patients were investigated: 19 with extramedullary disease, 11 with skeletal extramedullary disease and six with solitary extramedullary plasmacytoma. The first two groups showed the following results: del(17p13) 32% vs. 27%, del(13q14) 35% vs. 27%, MYC‐overrepresentation 28% vs. 18% and t(4;14) 37% vs. 18%. We detected an overall higher incidence of del(17p13) in both groups compared to data from bone marrow samples of multiple myeloma reported to date (range 7–16%). The solitary extramedullary plasmacytomas presented overall less cytogenetic aberrations than the other groups. Most important, three patients with extramedullary disease and one with skeletal extramedullary disease presented different FISH findings in the extramedullary tumour compared to their bone marrow plasma cells. del(17p13), occurring additional in three of four cases, seems a strong marker for extramedullary progression of myeloma.